Prevalence of Human Papilloma Virus (HPV) during urine test and clinical examination at Teritip Health Center , East Balikpapan , East Kalimantan - Purwanti, Helti; Dzikri, Achmad; Wirapuspita Wisnuwardani, Ratih (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Cervical cancer is primarily caused by Human Papillomavirus (HPV) infection, which is also a common cause of sexually transmitted diseases. HPV infection is present in 99.7% of cervical cancer cases Objective : The objective of this research was to outline the frequency of Human Papilloma Virus infection in adult and adolescent individuals who underwent HPV DNA PCR testing and clinical evaluation at Teritip Health Center, located in East Balikpapan, East Kalimantan in n December 2023 to June 2024 Research Methods/ A cross-sectional descriptive study was carried out to observe and gather information. 180 patients were recruited for HPV VCR and clinical examination by a midwifeImplementation Methods : Results : Six women were found to be positive for HPV among 180 participants Conclusion/Lesson Learned : It is needed for screening of HPV as a routine program.